If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8b + -10) + -2(6 + -3b) = 0 Reorder the terms: (-10 + 8b) + -2(6 + -3b) = 0 Remove parenthesis around (-10 + 8b) -10 + 8b + -2(6 + -3b) = 0 -10 + 8b + (6 * -2 + -3b * -2) = 0 -10 + 8b + (-12 + 6b) = 0 Reorder the terms: -10 + -12 + 8b + 6b = 0 Combine like terms: -10 + -12 = -22 -22 + 8b + 6b = 0 Combine like terms: 8b + 6b = 14b -22 + 14b = 0 Solving -22 + 14b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 14b = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 14b = 0 + 22 14b = 0 + 22 Combine like terms: 0 + 22 = 22 14b = 22 Divide each side by '14'. b = 1.571428571 Simplifying b = 1.571428571
| 1.29x+21+0.99=15 | | (4p-8)+(6p-7)= | | 2x+7-5=-17 | | 18x+1=15x+10 | | Sin(x)/2x | | 8-2(3y+5)= | | x^2-4x+70=0 | | -y+15=241 | | 6f+3(f+9)= | | 5x-(4)-2y+z=0 | | 3(u-9)=-54 | | (3x×sinx)/2x=sin40 | | -2(y+4)+4(2y+5)= | | 7(x+2)-6= | | 4n=2*12 | | x^2+y^2=3x-4y | | -3(y+5)-2y= | | 20=-5/2u | | -(x+1)-1= | | -(-y-4w+3)= | | (3y)=x-2x | | -5(-1)(-3)(-3)= | | 6(11-2)=54 | | P+9=56 | | 7+3*x=31 | | P+a=56 | | (3y)=x-2xsquared | | P+a=55 | | 5n-10=37 | | X=63-x/0.4 | | -3+(N+1)=12 | | wn2/3w=5/8 |